REGIONAL TRADE FLOWS AND EXPORT POTENTIAL OF KASHKADARYA: A SECTORAL ANALYSIS - Valiev Oybek; Ergashov Ziyodullo (Bright Mind Publishing, 2025)
This study examines the trade flows and export potential of the Kashkadarya region, a strategically important area in southern Uzbekistan. The region’s economic base is primarily composed of agricultural products, raw materials, and light manufacturing outputs, which form the core of its export portfolio. However, despite its rich natural resources, favorable climate, and growing production capacity, Kashkadarya’s integration into international markets remains limited. The paper identifies key sectors such as agro-processing, textile production, and construction materials as having significant unrealized export potential. Moreover, it highlights several structural and institutional challenges that constrain the region’s trade performance, including insufficient transport and logistics infrastructure, lack of market access support, and weak export promotion mechanisms. The study argues for the implementation of targeted regional development strategies and enhanced institutional support to address these constraints. Strengthening local value chains, improving export readiness among enterprises, and fostering cross-border trade linkages are essential to unlocking Kashkadarya’s full export potential and promoting balanced regional development within Uzbekistan.
Keywords: Kashkadarya, regional trade, export potential, trade flows, sectoral analysis, competitiveness, economic diversification.